IMPLEMENTASI KELURAHAN TANGGUH BENCANA DI BANDUNGREJOSARI KOTA MALANG - Ach. Apriyanto Romadhan; Taufik Rahman; Iradhad Taqwa Sihidi; Krishno Hadi (Dialogue : Jurnal Ilmu Administrasi Publik, 2022)
Malang City has the characteristics of disasters such as floods, landslides, and earthquakes, so community readiness in facing an upcoming disaster is needed. One of the coping strategies is through the Tangguh Disaster Village, which is a community capacity-building activity to protect themselves from the threat of disaster and the community as the main executor in dealing with disasters in disaster-prone areas. The purpose of this study was to determine the implementation of Tangguh Disaster Village in Bandungrejosari Village as an effort to reduce disaster risk in Malang City. The method used in this study is a qualitative method with a descriptive approach. Data collection techniques were obtained through observation, interviews, and documentation. The study results show that in implementing Disaster Resilience, after carrying out disaster socialization and simulation, the community, especially vulnerable groups, can know and understand what they should do when a disaster occurs through disaster risk reduction.